2020
DOI: 10.20473/j.djmkg.v53.i4.p212-216
|View full text |Cite
|
Sign up to set email alerts
|

Combining 10% propolis with carbonated hydroxyapatite to observe the RANKL expression in a rabbit’s alveolar bone

Abstract: Background: Periodontitis causes an increased receptor activator level in the nuclear factor-κβ ligand (RANKL), which is one of the inflammatory mediators that plays a role in osteoclastogenesis. The open flap debridement (OFD) technique is the preferred treatment when accompanied by regenerative periodontal treatment using guided tissue regeneration (GTR) and guided bone regeneration (GBR). Carbonated hydroxyapatite is a GBR material that serves as a scaffold and has strong osteoconductive properties for bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Specifically, RANKL controls osteoclastogenesis in bone remodeling and modeling, respectively, on the surfaces of osteoblasts and osteocytes. 15,20 This study is also in line with a previous study that demonstrated how gelatin could regulate RANKL-induced osteoclast differentiation through TGF-β1 signaling pathways. 21 As noted, OPG and RANKL play a role as mutual competitors, which was confirmed through this study's results, which showed that there is an increase in the amount of OPG compared with RANKL and RANK.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, RANKL controls osteoclastogenesis in bone remodeling and modeling, respectively, on the surfaces of osteoblasts and osteocytes. 15,20 This study is also in line with a previous study that demonstrated how gelatin could regulate RANKL-induced osteoclast differentiation through TGF-β1 signaling pathways. 21 As noted, OPG and RANKL play a role as mutual competitors, which was confirmed through this study's results, which showed that there is an increase in the amount of OPG compared with RANKL and RANK.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, propolis was shown to reduce osteoclastogenesis by modulating RANKL expression. Devitaningtyas et al (2020) found that the RANKL expression in rabbit’s alveolar bones was reduced by the propolis-incorporated with carbonated hydroxyapatite.…”
Section: Orthopedic/dentistry-related Biomaterialsmentioning
confidence: 98%
“…Limitations of this study was a short duration of the experiment. It was essential to conduct more research on the impact of the application of 10 % propolis and carbonate hydroxyapatite in OFD with a longer duration of observation ( Devitaningtyas et al, 2020 ).
Fig.
…”
Section: Propolismentioning
confidence: 99%
“…( Pereira et al, 2012 ). Additional findings have indicated that propolis can decrease osteoclastogenesis when administered in combination with carbonated hydroxyapatite ( Devitaningtyas et al, 2020 ).…”
Section: Propolismentioning
confidence: 99%
See 1 more Smart Citation